Effect of transient obstructive cholestasis on liver histology: a cross-sectional study - Mitsunaga, Thalita Mendes (2021)
BACKGROUND: The role of transient obstructive cholestasis on liver histology remains undetermined. OBJECTIVE: To investigate whether transient cholestasis impairs liver histology. DESIGN AND SETTING: Cross-sectional study at a public university hospital (UNICAMP), Brazil. METHODS: 169 individuals undergoing cholecystectomy, with or without cholestasis. were enrolled. Histopathological findings were correlated with clinical and biochemical characteristics. RESULTS: Biliary hepatopathy was more frequent in individuals with resolved cholestasis than in those with active obstruction or no jaundice (P < 0.01), as also were fibrosis and ductular proliferation (P = 0.02). Cholestasis was commoner in individuals with resolved obstruction than in those with no history (P < 0.01)or active cholestasis (P < 0.05). Biliary hepatopathy was associated with longer duration of cholestasis (P < 0.001) and higher bilirubin levels (P = 0.02) in individuals with active obstruction; with lower body mass index (P = 0.02) and longer cholestasis (P < 0.001) in individuals with resolved obstruction; and with longer cholestasis (P < 0.001) and longer interval between endoscopic retrograde cholangiopancreatography and surgery (P = 0.03) overall. In individuals with active obstruction, duration of cholestasis (R = 0.7; P < 0.001) and bilirubin levels (R = 0.6; P = 0.004) were independently correlated with cholestasis severity. Duration of cholestasis (R = 0.7; P < 0.001) was independently correlated with ductular proliferation severity. CONCLUSIONS: Transient cholestasis was associated with significant histopathological changes, even after its resolution. Longer duration of obstruction correlated with greater severity of histopathological changes, especially cholestasis and ductular proliferation. This emphasizes the need for early treatment of obstructive cholestasis.